Pengembangan Potensi Desa Blahkiuh Sebagai Wisata Perdesaan Di Kabupaten Badung (Jurnal Destinasi Pariwisata, 2025)
This study aims to examine the potential and development strategies of Blahkiuh Village as a rural tourism destination in Badung Regency. The research was conducted due to the disparity in tourism development between South Badung, which has grown rapidly, and North Badung, which tends to lag behind. Blahkiuh Village was selected because it has diverse tourism potentials that have not yet been optimally developed. This research employs a descriptive qualitative method with data collected through observation, interviews, literature review, and documentation. Data analysis was carried out interactively through data reduction, data presentation, and conclusion drawing. The findings indicate that Blahkiuh Village's tourism potential is categorized into three main types: natural, cultural, and artificial attractions. The natural potential includes Subak Blahkiuh and Subak Sangeh rice fields, which offer ecotourism appeal. The cultural potential consists of Pura Luhur Giri Kusuma, the Ngerebeg Matiti Suara tradition, and performing arts such as Kecak and Joged Bumbung dances, which represent the village’s unique identity. Meanwhile, the artificial potential includes Taman Gili Dukuh, Tirta Arum Swimming Pool, Dukuh Camping Ground, and culinary specialties such as Lawar Sapi Men Basug and Dadong Located. Based on the Tourism Area Life Cycle (TALC) model, the development of tourism in Blahkiuh Village is currently at the involvement stage. To advance to the development stage, strategic efforts based on Sapta Wisata (Seven Pillars of Tourism Development) are required by optimizing local potentials, strengthening collaboration between the village government, local communities, and stakeholders, and prioritizing sustainability. Therefore, Blahkiuh Village holds significant potential to develop into a competitive and sustainable rural tourism destination rooted in local wisdom
Keywords: rural tourism; tourism development; Blahkiuh